Global attractivity without stability for Liénard type systems - Marian Mureşan (International Journal of Mathematics and Mathematical Sciences)
We are concerned with some conditions such as the trivial solution of a planar system of differential equations (including the Liénard system) that is globally attractive but not stable. We emphasize the connection with some nonoscillatory conditions. The results are related to the previous ones obtained by Hara in 1993.